‘Living a life less ordinary’: exploring the experiences of Australian men who have acquired HIV overseas - Brown, G.; Ellard, J.; Mooney-Somers, J.; Prestage, G.; Crawford, Gemma; Langdon, T. (C S I R O Publishing, 2014)
Background: Increasing international mobility has led to a growth of cross-border HIV transmission around the world. In Australia, increasing rates of HIV infections acquired overseas have been reported, particularly among men. This qualitative study explored experiences and risk perceptions of 14 Australian men who acquired HIV while living or travelling overseas from the year 2000. Methods: Symbolic interaction provided the study’s theoretical perspective and analytical framework. Australian men living with HIV who were aged 18 years and older, believed they had acquired their infection while working or travelling overseas during or after the year 2000, and were diagnosed from 2003 onwards were eligible to participate. A semistructured interview schedule was developed and tested for content validity with the study reference group. Analysis was conducted using an adapted form of grounded theory to form the basis for the development of the experiences domains. Results: Analysis produced four domains of experience: (1) a fantasy realised, (2) escaping and finding a new self or life, (3) living a life less ordinary and (4) living local but still an outsider. The description of the four experience domains highlights how risk generally, particularly sexual risk, did or did not feature in these men’s understanding of their experiences. Conclusion: Perceptions and experiences of long-term travel played a decisive role for men who acquired HIV when travelling overseas. Appealing to desired experiences such as connection to local culture or sustaining a new or adventurous life may provide important implications for guiding health promotion programs and policy.